Pengaruh Minuman Probiotik Lactobacillus casei shirota strain Terhadap Pelepasan Ion Nikel Braket Stainless Steel - Meli Oktafiani; Aria Fransiska; Nelvi Yohana (Andalas Dental Journal, 2023)
The stainless steel bracket is the most commonly used fixed orthodontic component in orthodontic treatment. The brackets in the oral cavity for a long time can cause the release of metal ions, one of which is nickel ions. Food and beverages can change the pH of the oral environment, such as probiotic beverages. The probiotic beverage with Lactobacillus casei shirota strain has a pH of around 3 – 4,5. Low pH can increase nickel ion release and allow hypersensitivity reactions to occur. The purpose of this study was to determine the effect of Lactobacillus casei shirota strain probiotic beverage on the release of nickel ions from stainless steel brackets. This research was a laboratory experimental study with a post-test-only control group design with 10 samples. Each stainless-steel bracket sample was immersed in 50 ml of artificial saliva as a control group and 50 ml of Lactobacillus casei shirota strain probiotic beverage as a treatment group. Samples were immersed for 18 hours and 15 minutes in an incubator at 37˚C. The release of nickel ions was tested using Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES). The results were analyzed by a parametric Independent t-test. The average release of nickel ions in the treatment group was 9,69 ppm and the control group was 9,22 ppm. Independent t-test showed a significant difference (p<0,05) in the mean of the artificial saliva and the Lactobacillus casei shirota strain probiotic beverage. The release of nickel ions from stainless steel bracket in Lactobacillus casei shirota strain probiotic beverage was greater than artificial saliva.